Water in Circular Economy and Resilience - Delgado, Anna; Rodriguez, Diego J.; Amadei, Carlo A.; Makino, Midori (World Bank, Washington, DC, 2021)
Rethinking urban water through the circular economy and resilience lenses offers an opportunity to transform the urban water sector and deliver water supply and sanitation services in a more sustainable, inclusive, efficient, and resilient way. Circular Economy principles have emerged as a response to the current unsustainable linear model of "take, make, consume, and waste." In a circular economy, the full value of water – as a service, an input to processes, a source of energy and a carrier of nutrients and other materials – is recognized and captured. This report presents the Water in Circular Economy and Resilience (WICER) Framework together with global case studies that show the benefits of becoming circular and resilient. It describes the key actions needed to achieve three main outcomes: 1) deliver resilient and inclusive services, 2) design out waste and pollution, and 3) preserve and regenerate natural systems. The report sets out to demystify circular economy by showing that both high-income and low-income countries can benefit from it.